2020
DOI: 10.3390/su122410240
|View full text |Cite
|
Sign up to set email alerts
|

Performance of High Rap Half-Warm Mix Asphalt

Abstract: The current global situation regarding climate change makes it necessary to promote the circular economy and the use of more environmentally friendly technologies in the construction sector. To that end, it is of interest to deepen our understanding of the performance of half-warm mix asphalt (HWMA) manufactured with high proportions of reclaimed asphalt pavement (RAP). Thus, in the present study, a laboratory analysis was carried out in which the behavior of HWMA manufactured with 100% RAP and without rejuven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Engine oil's characteristics degrade with continued usage over time, and if it is not disposed of properly, it poses a threat to both the environment and human health. Due to the demand from the economy and environment to properly manage waste, the interest in reusing WEO has increased [11]. Several researchers have looked into the idea of employing WEO to rejuvenate the characteristics of aged asphalt binders [12].…”
Section: Introductionmentioning
confidence: 99%
“…Engine oil's characteristics degrade with continued usage over time, and if it is not disposed of properly, it poses a threat to both the environment and human health. Due to the demand from the economy and environment to properly manage waste, the interest in reusing WEO has increased [11]. Several researchers have looked into the idea of employing WEO to rejuvenate the characteristics of aged asphalt binders [12].…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used methods for producing warm-mix asphalt include the utilization of proprietary techniques and additives (e.g., liquid and solid warm mix additives) [ 5 , 6 , 7 ], asphalt binder foaming using zeolite and other water-bearing minerals [ 8 , 9 , 10 , 11 , 12 ], direct water injection [ 13 , 14 , 15 , 16 ] and use of bio-based fluxing agents [ 17 , 18 , 19 , 20 , 21 ]. In the recent years techniques enabling production of half-warm mix asphalt mixtures have also gained significant attention [ 22 , 23 , 24 ]. One of the added benefits of warm mix asphalt techniques is the possibility of extending the hauling distance of the mixture [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the early damage to asphalt pavement is intensely related to water damage [2,9]. Water damage has become one of the main reasons for affecting the service life of asphalt pavement and reducing the service performance of asphalt pavement [10,11]. Therefore, the evaluation of the water stability of HRM is particularly important.…”
Section: Introductionmentioning
confidence: 99%